Autologous platelet-rich plasma for the treatment of interstitial cystitis/bladder pain syndrome in women: evaluation of clinical efficacy - V. L. Medvedev; S. N. Lepetunov; M. I. Kogan (Вестник урологии, 2023)
Introduction. The pathogenetic theory of interstitial cystitis/bladder pain syndrome (IC / BPS) development declares that due to vascular changes and trophic disorders in the bladder wall, a complex of dystrophic, necrobiotic and sclerotic processes develops, involving all layers of the bladder wall with the subsequent development of fibrosis. Therapy of moderate-to-severe symptoms of IC/BPS that recommended in EAU guidelines is not so effective.Objective. To evaluate the results of intradetrusor autologous platelet-rich plasma (PRP) injections in female IC / BPS-patients.Matherials & methods. A single-centre controlled randomized prospective trial that includes 85 women from 20 to 79 years old and with average disease duration of 4.8 ± 2.1 years. They were divided into two groups: group 1 — 35 patients were treated with total of five cystoscopies and hydrodistension, each once in two weeks for 10 weeks; group 2 — 50 patients were treated with total of 5 intradetrusor PRP-injection (mean platelet concentration was 982 х 103/l) into 20 – 22 points, each once in two weeks. We assessed pain (VAS-scale), urgency and frequency (PUF-scale, IUS-scale), bladder urinary, Global Response Assessment (GRA), bladder diary and bladder capacity before treatment, after one and 12 months.Results. Conventional IC/BPS therapy leads to a significant reduction in symptoms one month after its completion, and a similar pattern of symptoms and signs is observed in the PRP-treatment group. However, in group 1, negative dynamics is further determined up to 12 months, but the indicators do not reach the initial values. In contrast, in group 2, we found stabilisation of pain severity and improvement of all other symptoms and signs by 12 months compared to baseline and one month after the completion of PRP-therapy.Conclusion. The developed method of PRP-therapy of IC/BPS has high efficacy not only at the treatment completion, but also at monitoring of patients for 24 months. PRP-therapy combined with classical treatment will probably have a higher level of efficacy both in terms of symptoms and signs of the disease over a long-term monitoring.